Author stance and engagement in research articles on educational equity: A comparison between Chinese and Australian authors - Chen Li; Rining Wei (PLoS ONE, 2026)
Author stance and engagement illustrate how the writer interacts with readers in academic texts. Although disciplinary variations in stance-taking and engagement strategies have been extensively documented, scholarly attention has predominantly focused on cross-disciplinary comparisons with limited attention paid to the use of these communicative strategies within specific topical domains. This study aims to examine author stance and engagement in English research articles on educational equity authored by Chinese and Australian authors. Drawing on Hyland’s framework of stance and engagement, it employs a quantitative analysis of interactional metadiscourse markers and engagement devices using the software Wordsmith 4.0 and a log-likelihood calculator. Additionally, the qualitative keyword analysis is conducted to examine other linguistic features that may reflect author stance. The results indicate a statistically significant overuse of stance markers and engagement devices by Chinese authors compared to Australian authors, alongside a more cautious writing style exhibited by Australian authors. Keyword analysis further reveals that Chinese authors tend to adopt a holistic view of educational equity and its relation to different contexts, whereas Australian authors emphasize in-depth research on the topic from diverse perspectives. Cultural interpretations highlight the influence of collective culture versus individualistic culture, analytic vs. holistic thinking, the notion of xin (integrity), and conceptions of the self. The research findings can assist authors in recognizing cultural differences across discourse communities and in adopting appropriate stance markers and engagement devices in their academic writing.